Energy efficiency and thermal comfort in Wood Frame constructions (Research, Society and Development, 2022)
The objective of the present work was to evaluate and analyze the issue of energy efficiency and thermal comfort present in the Wood Frame constructive system, examining concepts about energy efficiency and its importance, as well as current legislation, energy efficiency measures, identification of thermal comfort variables and describing the construction process of the Wood Frame system. The study was carried out through a bibliographic review, that is, a survey to review published works on the subject studied, in order to endorse the topic addressed, rigorously evaluating, impartial and comprehensive information about scientific research. There is no specific standard for the Wood frame construction method, the development of buildings built in Wood Frame is evaluated following the criteria and requirements of NBR15575 (2013) - Housing buildings - Performance. However, it is necessary to analyze whether these constructions meet the criteria required by Brazilian standards, not only the energy efficiency and comfort of the building user, with the objective of analyzing the energy efficiency and thermal comfort present in the Wood Frame constructive system. Finally, the Wood Frame system is the best constructive option, obtaining significant energy efficiency, because when taking into account all the materials that permeate the system such as wood, plasterboard and rock wool. in addition to allowing greater thermal comfort and environmental support in the absorption of carbon dioxide and the production of oxygen in the atmosphere.